Optimizing Indonesian Language Learning During the Covid-19 Pandemic in Elementary Schools - Nur Samsiyah (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Learning during the pandemic has an impact on student learning activities in learning Indonesian. This impact causes learning to be carried out online. The purpose of this study was to find out how the teacher's strategy was to optimize Indonesian language learning in elementary schools during the covid-19 pandemic. This research is descriptive qualitative research that examines the strategies of elementary school teachers in optimizing online learning. Data collection techniques using observation, interviews and questionnaires. The research was conducted at an elementary school in Madiun with 10 grade 4 teachers as the subject. The results of optimizing Indonesian language learning show that students learn Indonesian using thematic books with Whatsapp group application services, google meet, google classroom, Microsoft 365, google form, social media. The results of the assessment are carried out using quizzes or tests in the form of assignments.